Using dissipation factor method in testing the ash sintering process of cereal pellet and coal fuels. (1st July 2022) - Nowak-Woźny, Dorota; Ferens, Wiesław; Wach, Janusz
Abstract: The aim of the paper is to present the results of alternating current electrical tests made on ashes of selected solid fuels (biomass and coal from Polish mines). This work is meant to supplement the current state of knowledge with an alternating current method for assessing the state of sintering of biomass and coal ash in relation to thermogravimetric and calorimetric tests, statistical (oxide indicators), sintering temperatures i.e. ash fusion test and analyses of multicomponent thermodynamic equilibria. An ultimate and proximate analysis were made for all fuels. Thermogravimetry analysis and differential scanning calorimetry measurements have been carried out for the sintering process of ash in the temperature range up to 900 °C. The thermodynamic analysis has been performed using the FactSage software. The dissipation factor measurements of the sintering process of ash have been carried out. A model of dissipation factor change during sintering has been proposed, which then has been used to calculate the activation energy of the ash sintering process for all fuels. The obtained data has been compared with data available in literature. The good correspondence between them leads to the conclusion that both the assumed model and the adopted measurement method are correct. Highlights: AC electrical test for assessing the ash slagging and fouling hazards. Mechanism of coal and biomass ash sintering process – activation energy. Modelling of coal and biomass ash sintering using FactSage software. The AC test proved useful for assessing of ash transformation activation energies. The dispersion coefficient test is a good indicator for assessing slagging and fouling hazards.